(untitled) (KYAMC Journal, 2026)
Background: Burning Mouth Syndrome (BMS) is a chronic condition marked by a persistent burning sensation in the mouth, often without visible lesions or a clear cause. Recent studies have suggested a potential link between iron deficiency and BMS, particularly in populations with low serum iron levels. Objectives: This study aims to investigate the relationship between serum iron levels and the prevalence of BMS in a cohort of 190 patients, with a focus on age and gender as contributing factors. Materials and Methods: A cross-sectional observational study was conducted on 190 patients presenting with oral burning sensations. Serum iron levels were measured using standard laboratory methods, and statistical analyses were performed using SPSS software. The study included stratified analyses by age and gender to identify potential patterns in serum iron deficiency. Results: The analysis revealed that 85.3% of the patients had low serum iron levels, with a significant correlation between low iron levels and the presence of BMS symptoms. Stratified analysis indicated that iron deficiency was particularly prevalent among female patients and those over 60 years of age. Conclusion: The findings of this study suggest that serum iron deficiency is a significant contributor to BMS, particularly in women and older adults. These results underscore the importance of routine serum iron assessments in patients with unexplained oral burning sensations, potentially guiding more targeted treatment strategies.